Are odorant constituents of herbal tea transferred into human milk? - Denzer-Lippmann, Melanie; Kirsch, Frauke; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2015)
The present study investigates aroma transfer from commercial nursing tea, consumed in the maternal diet, into human milk by correlating sensory assessments with quantitative analytical data. The target terpenes were quantified in milk (expressed before and after tea consumption) and tea samples via gas chromatography-mass spectrometry (GC-MS) using stable isotope dilution assays (volunteer donors n = 5). Sensory analyses were carried out on different milk samples from a single donor, sampled before (blank) and at different times after tea ingestion. Quantitative analysis revealed that no significant odorant transfer into milk was observed after lactating women drank the tea. The comparative sensorial analysis of milk samples expressed before and after tea consumption confirmed that tea ingestion had no significant influence on the odor profile of human milk.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.areodo
Keywords: herbal tea; human milk; odorant transfer; SAFE (solvent-assisted flavor evaporation); sensory